Does government ownership matter? Comparative study between GLCS and NGLCS in Malaysia - Ting I.W.K.; Lean H.H. (World Scientific Publishing Co. Pte Ltd, 2023)
comparative study; firm ownership; industrial performance; state owned enterprise; Malaysia